Housing choice among students at the University of the Philippines in the Visayas, Miag-ao, Iloilo Campus - Celiz, Chanda Nhell Palasol
The study identified and described the factors affecting the housing choice among students studying at the University of the Philippines in the Visayas (UPV), Miag-ao campus., A structured questionnaire was used to gather primary data from the 245 respondents who were undergraduate students, staying at UPV dormitories (184) and private dormitories and boarding houses (61). They were selected using proportional stratified random sampling. The data were processed using the SPSS 8.0 software. Logistic regression was used as an estimation technique. The significant findings of the study are:(1)female respondents coming from outside of Iloilo were most likely to rent in a particular housing unit in Miag-ao; (2)the housing unit first preferred by the respondents was more likely to be chosen; (3)UPV dormitories did not allow or had no facilities for cooking, washing and ironing of clothes; (4)there was a difference in the respondents' ranking of preferred characteristics of the `ideal' housing unit and the characteristics of the currently occupied housing units; (5)the significant factors that affect the housing choice among the respondents were total monthly family income, total monthly rent, perceived accessibility of housing unit to grocery/department store and if whether or not the current housing unit was the first preference; and, (6)the main problem cited during the time of choosing and looking for a particular housing units were the limited availability of slots and the high rent asked.